Analisis Strategi Pemasaran terhadap Penjualan Minyak Kelapa Sawit (CPO) pada PT. Perkebunan Nusantara III (PERSERO) - Lubis, Faradilla Fakhirah; Nasti, Nilawati; Sonata, Ilham (Universitas Islam Islam Sumatera Utara, 2023)
One critical commodity in Indonesia is crude palm oil, or CPO. In order to boost palm oil sales, this research use SWOT analysis to identify the most effective marketing methods. Things like assessing possibilities in the market, creating marketing strategies, designing marketing programs, and coordinating marketing activities are essentially the focus of the company's marketing strategy. This study combines primary and secondary sources to provide a descriptive account of the phenomena under investigation. Using the IFAS and EFAS matrices, a number of tests are conducted, including SWOT analysis tests. According to the study's findings, the x-axis of the SWOT diagram is the IFAS matrix value of 0.06, and the y-axis is the EFAS matrix test result value of 1.12. When the IFAS and EFAS matrices are applied to the SWOT diagram, the findings show that the company's internal factors are strong in area I. Based on the SWOT analysis, PT Perkebunan Nusantara III Medan has an aggressive approach that aims to build on current strengths while also improving and maintaining them. The firm is in kudran I, according to the SWOT diagram